Lembar Kerja Mahasiswa based on Tri N Ki Hadjar Dewantara in science education - Yohana Baptista; Safitri Yosita Ratri (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study addresses the limited development of teaching materials integrating the Tri N philosophy of Ki Hadjar Dewantara (Niteni, Nirokke, and Nambahi) in science education, particularly for prospective elementary school teachers. The research aims to develop Tri N-based Lembar Kerja Mahasiswa (LKM) and evaluate its feasibility and effectiveness in supporting science learning. A research and development (R&D) approach was employed using the 4D model, consisting of define, design, develop, and disseminate stages. Data were collected through validation questionnaires completed by subject matter and media experts, and analyzed quantitatively. The results indicate that the developed LKM achieved a very high validity score, with an average of 93%, categorized as highly feasible. Furthermore, effectiveness testing using a t-test showed a significance value of 0.02 (< 0.05), indicating a significant improvement in student learning outcomes in the experimental group compared to the control group. These findings suggest that Tri N-based LKM is effective in promoting active, meaningful, and contextual learning, and can enhance students’ understanding and engagement in science education.